1999
DOI: 10.1074/jbc.274.23.16269
|View full text |Cite
|
Sign up to set email alerts
|

Topological and Functional Analysis of the Human Reduced Folate Carrier by Hemagglutinin Epitope Insertion

Abstract: The membrane topology of the human reduced folate carrier protein (591 amino acids) was assessed by single insertions of the hemagglutinin epitope into nine sites of the protein. Reduced folate carrier-deficient Chinese hamster ovary cells expressing each of these constructs were probed with anti-hemagglutinin epitope monoclonal antibodies to assess whether the insertion was exposed to the external environment or to the cytoplasm. The results are consistent with the 12-transmembrane topology predicted for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 54 publications
9
73
0
Order By: Relevance
“…It is expressed as a membrane protein in a wide variety of tissues and cell types (1,3,4); and although highly conserved at the amino acid level, it varies in predicted size from 58 to 85 kDa depending upon the species (5-7). Hydrophobicity analyses have indicated that the RFC protein has 12 transmembrane-spanning segments with the N and C termini located intracellularly and a large intracellular loop between transmembrane domain (TM) 6 and TM7 (8). Epitope insertions into the predicted major loops (8,9) and N-glycosylation scanning mutagenesis (9) support this model, although the latter study suggests that the C-terminal portion of the protein may demonstrate an alternative topology.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…It is expressed as a membrane protein in a wide variety of tissues and cell types (1,3,4); and although highly conserved at the amino acid level, it varies in predicted size from 58 to 85 kDa depending upon the species (5-7). Hydrophobicity analyses have indicated that the RFC protein has 12 transmembrane-spanning segments with the N and C termini located intracellularly and a large intracellular loop between transmembrane domain (TM) 6 and TM7 (8). Epitope insertions into the predicted major loops (8,9) and N-glycosylation scanning mutagenesis (9) support this model, although the latter study suggests that the C-terminal portion of the protein may demonstrate an alternative topology.…”
mentioning
confidence: 75%
“…Predicted topology of RFC. The topology is based on hydropathy plots and epitope insertion analysis (8,9). Circled residues indicate those conserved among hamster, human, rat, and mouse species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, low-pH transport activity is inhibited in freshly isolated intestinal epithelial cells by an antibody to the NH 2 and COOH termini of RFC (4). It is unclear, however, how this antibody could block the function of this carrier in intact cells when it is directed to domains located in the cytoplasm (8). Transfection of RFC into IEC-6 cells resulted in the induction of a low-pH transport activity (19).…”
Section: Discussionmentioning
confidence: 99%
“…The RFC is an integral membrane protein with 12 putative transmembrane domains. 9,11,14 A large number of RFC gene mutations leading to an antifolate-resistant phenotype have been described in rodent and human cell lines. [15][16][17][18][19][20][21] Although mutations have been identified throughout the RFC coding region, they appear to be disproportionately clustered within the first putative transmembrane domain (eg G44E, E45K, S46N, I48F).…”
Section: Introductionmentioning
confidence: 99%